Flexible force sensitive frequency reconfigurable antenna base on stretchable conductive fabric. (12th May 2022) - Shao, Li; Tang, Xinyue; Yang, Yujie; Wei, Dacheng; Lin, Yuanchang; He, Guotian; Wei, Dapeng
Abstract: With the development of wireless technology and flexible electronics, flexible frequency reconfigurable antennas have been directly used as sensors to detect mechanical signals. As an important frequency reconfigurable antenna, microstrip antenna has been widely studied in the field of flexible and flexible electronics in recent years. However, the stretchability of microstrip antennas usually comes at the cost of reducing the conductivity of the radiated conductor. Here, we report a flexible force sensitive frequency reconfigurable microstrip antenna, which fabricated by silver fiber conductive fabric with a double-wire braided structure. In order to increase the detection of pressure, an elastic dielectric layer with a microhemispheric array was introduced into the microstrip antenna to extend the frequency band width of the reconfigurable antenna. The relative frequency of the antenna varied from 0% to −12.9%, and the sensing sensitivity was −1.9 kPa −1 . As potential applications, we demonstrate the use of a flexible frequency reconfigurable antenna base on stretchable conductive fabric as a strain sensor capable of measuring bending angle and movements of a human finger. The change in the resonance frequency with the externally applied tensile strain in this antenna design has a sensitivity of 3.448, manifesting a 4.19- and a 13.79-fold increase of sensitivity when compared to those in previous reports that used arched or both-planes serpentine rectangular microstrip antenna. This is of great significance for the application of wearable antenna in wireless mechanical sensing technology.